Age-related prevalence of osteoporosis and fragility fractures: real-world data from an Austrian Menopause and Osteoporosis Clinic. (4th March 2017) - Boschitsch, E. P.; Durchschlag, E.; Dimai, H. P.
Abstract: Objectives: Age and bone mineral density (BMD) are the most relevant determinants for public health authorities to govern the management of osteoporosis. The objectives of this study were to determine the age-related prevalence of osteopenia and osteoporosis according to WHO criteria and fragility fractures in middle-aged and older women. Methods: Women ≥40 years, who were referred to a menopause and osteoporosis outpatient clinic for BMD measurements, were assessed for patient characteristics, BMD and previous fragility fractures of the hip, the distal forearm and the vertebrae. Only records of their initial consultations were used for data analysis. Results: Between 1990 and 2012, 99, 399 women, mean age 56.1 years, were referred to the clinic for BMD testing. Of the total population, 52.5% showed normal, 34.0% osteopenic and 13.5% osteoporotic BMD. Fragility fractures were reported by 6540 patients, with 3070 (47%) non-vertebral fractures, namely 2518 (38.5%) distal forearm and 552 (8.4%) hip fractures; 66.8% of patients with the non-vertebral fractures were <65 years. Conclusion: The prevalence of osteoporosis and fragility fractures in middle-aged women, < 65 years, is hitherto under-recognized. Measuring BMD alone is not sufficient to identify patients at risk for fractures. Supplemental screening for clinical risk factors already during perimenopause may be advantageous.